Similarities and differences in the regulation of HoxD genes during chick and mouse limb development - Yakushiji-Kaminatsui, Nayuta (PLoS Biol, 2018)
In all tetrapods examined thus far, the development and patterning of limbs require the activation of gene members of the HoxD cluster. In mammals, they are regulated by a complex bimodal process that controls first the proximal patterning and then the distal structure. During the shift from the former to the latter regulation, this bimodal regulatory mechanism allows the production of a domain with low Hoxd gene expression, at which both telomeric (T-DOM) and centromeric regulatory domains (C-DOM) are silent. These cells generate the future wrist and ankle articulations. We analyzed the implementation of this regulatory mechanism in chicken, i.e., in an animal for which large morphological differences exist between fore- and hindlimbs. We report that although this bimodal regulation is globally conserved between the mouse and the chick, some important modifications evolved at least between these two model systems, in particular regarding the activity of specific enhancers, the width of the TAD boundary separating the two regulations, and the comparison between the forelimb versus hindlimb regulatory controls. At least one aspect of these regulations seems to be more conserved between chick and bats than with mouse, which may relate to the extent to which forelimbs and hindlimbs of these various animals differ in their morphologies.